Waste treatments in the European Union: A comparative analysis across its member states - María Pilar López-Portillo; Guillermo Martínez-Jiménez; Eva Ropero-Moriones; María Concepción Saavedra-Serrano (Heliyon, 2021)
Waste treatments, which add value to the production system, may contribute to achieving a more circular economy. These recovery treatments are material recycling, composting and digestion, and energy recovery. This paper analyses recycling activity and other waste treatments in the European Union (EU), using a comparative approach among its Member States. In order to do this, some factors that may influence these treatments are studied, such as economic development, R&D expenditure, resource productivity and the period of each country's permanence in the EU. Although waste treatment rates have converged between countries from 2010 to 2018, there are still differences. In order to explain these differences, the countries have been grouped into three clusters through a K-means non-hierarchical cluster statistical analysis. Subsequently, a non-parametric Kruskal-Wallis test has been applied to examine whether these observed differences are significant in the last year of the period analysed. The results corroborate the main hypothesis of this research: there are various behaviour patterns in waste treatments according to the country clusters and based on their real GDP per capita, R&D expenditure, resource productivity and number of years as an EU member.